Analysis of Neonatal Admission Patterns and Clinical Profiles in a Tertiary Care Center: Focus on Neonates Transferred from the Delivery Room to the Neonatal Intensive Care Unit - Khanal, Babita; Yadav, Sunil Kumar; Pokhrel, Sandip; Singh, Sandip Kumar; Baral, Gehanath; Kafle, Prakash (Journal of Nobel Medical College, 2023)
Background: Neonatal mortality rate is very high in developing countries despite of advancement in perinatal and neonatal care with reduced neonatal mortality rate in many developed countries. This study aims to identify the reasons of admitting neonates for intensive care after vaginal delivery and their outcome.Materials and Methods: This is an observational descriptive study conducted for over a year at Nobel Medical College Teaching Hospital which included newborns delivered vaginally within the hospital. Demographic data of newborn and mother was obtained, birth weight, reason for admission and final outcome were documented. Outcomes were classified as improved with recovery, mortality and discharge on request prior to recovery. Descriptive statistics such as mean, percentage and standard deviation were obtained.Results: Total 117 neonates were admitted to intensive care out of 3452 vaginal deliveries with male to female ratio of 1.9:2. There were 60 (51.3%) preterm, 55 (47%) full term and 2 (1.7%) post term; and 68 (58.1%) were low birth weight. Prematurity with respiratory distress syndrome was the most common cause of admission (34.2%) along with birth asphyxia (29, 24.8%) and meconium aspiration syndrome (20, 17.1%). Positive Airway Pressure was required in 42 (35.9%). Blood Culture positive growth was seen in 17.9% with most common organism being Staphylococcus aureus. Mean stay was 3.75±2.49 days andmortality in the study population was 6.8%.Conclusion: Prematurity with respiratory distress syndrome, birth asphyxia and meconium aspiration syndrome were major indications for admission of newborns delivered via vaginal deliveries to neonatal intensive care unit. One-fourth required mechanical ventilation.